Welfare Capitalism in Southeast Asia - Ramesh, M. author. aut Link
XII, 217 p.
Keywords: This is the only in-depth study of social policies in Southeast Asia. It compares social security, health, and education policies in Indonesia, Malaysia, the Philippines, Singapore and Thailand. After describing the policies and assessing their adequacy and equity implications, it examines the forces that have shaped them. It concludes that social programs (except for primary education) in the region are both inadequate and inequitable. It argues that the reason for this is political rather than cultural or socio-economic.